The Use of Natural Resources for Wastewater Treatment - Nadiatul Adilah, Ahmad Abdul Ghani; Siew, Phui Moon; Edriyana, Abd Aziz; Abdul Syukor, Abd Razak; Suryati, Sulaiman; Hasmanie, Abdul Halim (2014)
Wastewater contains of different types of contaminants will bring impacts to the environment and the aquatic life. Therefore wastewater is needed to be treated before it is discharged into river. Activated carbon produce from coconut shell is one of natural resources that is believed can treat the wastewater by removing those contaminated substances. This study identified the potential of these natural resources in the filter system to improve the wastewater quality. Wastewater from KK3 cafe at Universiti Malaysia Pahang was used to be test with this carbon filter system. Four parameters include turbidity, Total Suspended Solid (TSS), Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) were check to identify the wastewater quality after using this carbon filter. The water quality of wastewater at KK3 café was improved after using carbon filter. The percentage of wastewater parameter removal in range of 60.63% to 97.48%. This carbon filter was recommended to be set up at KK3 cafe at Universiti Malaysia Pahang as to pre-treat the wastewater before it is discharged into river.